2018
DOI: 10.1111/cen.13733
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and IGF‐1 in relation to body composition and bone mineralization of preterm‐born children from infancy to 8 years

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. Funding informationThe original randomized controlled trial was supported by an unrestricted research grant from Friesland Campina, Amersfoort, the Netherlands. Friesland Campina also provided the formulas. CR was supported by an u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
2
4
1
Order By: Relevance
“…Nevertheless, given the sample size and observational nature of this study, the evidence for this hypothesis is inconclusive and remains speculative. Moreover, this is in contrast to reports by Ruys and colleagues who found a positive association between IGF-I and fat free mass as well as fat mass measured in preterm infants at term equivalent age, implying that IGF-I relates to overall growth rather than body composition [ 11 ]. However, in relation to later measurements of body composition, others did find IGF-I to relate to body composition.…”
Section: Discussioncontrasting
confidence: 96%
“…Nevertheless, given the sample size and observational nature of this study, the evidence for this hypothesis is inconclusive and remains speculative. Moreover, this is in contrast to reports by Ruys and colleagues who found a positive association between IGF-I and fat free mass as well as fat mass measured in preterm infants at term equivalent age, implying that IGF-I relates to overall growth rather than body composition [ 11 ]. However, in relation to later measurements of body composition, others did find IGF-I to relate to body composition.…”
Section: Discussioncontrasting
confidence: 96%
“…Higher MOM IGF-1 concentrations at 4 months' corrected age were instead associated with a greater waist circumference. Previous studies around circulating IGF-1 during infancy confirm the relationship between IGF-1 and leptin concentrations and the association of both these compounds with infant fat and, to a lesser extent, lean mass (60)(61)(62). Previous studies have reported on a strong correlation between waist circumference and fat mass (63) although in our cohort IGF-1 did not show any association with fat mass.…”
Section: Discussionsupporting
confidence: 66%
“…The robust correlation between IGF-I and adipose tissue in VPT-LBW men indicate that IGF-I might be of special importance in this group. During infancy and childhood, up to 8 years, leptin but also in some extent IGF-I positively correlated with fat mass in PT-LBW 39 .…”
Section: Discussionmentioning
confidence: 87%